2 - La coopération sud-sud : le plan de Lagos et l’indépendance de l’Afrique - A. BENACHENHOU (Africa Development, 1982)
Benachenhou's article is set within the context of a general overview of the Lagos Plan of Action (LPA). After giving the reasons why this document should be considered seriously, he reviews its strong points and its weak points as well as the national and international conditions of its implementation before concluding with a concise analysis of the challen- ge of the Berg Report. Analysing the new elements contained in the LPA in the first part, the author sets them within the context of a new context of development which no longer perceives development as a direct by-product of the world economic system. He further sets them within the context of a stricter control of foreign operators and African natural resources and within that of new approaches adopted by the LPA in some sectors of economic activities. Finally he sets tnem against the background of the condemnation of Africa's food dependence and the need for self-sufficiency in this respect. In spite of these new elements, however, the LPA document contains a numoer of ambiguities and points on which it remains silent and which are reviewed by the author in his article. In the second part of his article, Benachenhou notes that the imple- mentation of the LPA will depend upon the exogenous and endogenous circumstances which will prevail duriną the next two decades. Indeed there are some constraints in the international situation which should be taken into consideration, yet this situation also offers possibilities which should be exploited. Besides non-negligible economic potentials characterizing the national situations, the frequent lack of actual national projects for a self- reliant development can also be noted. The author concludes his article with a brief analysis of the challenge of the World Bank Report for Africa. This report which is utter con- tradiction with the principles of the LPA, expresses the view that African development can only be the by-product of world economic development and can only be fully attained through the free play of the market forces.